Antibacterial Activity of Red Ginger (Zingiber officinale var. rubrum) and Black Turmeric (Curcuma caesia) Extracts as Growth Inhibitors of Klebsiella pneumonia - Siti Juariah, Siti Juariah; Fazleen I.A. Bakar, Fazleen I.A. Bakar; Mohd F.A. Bakar, Mohd F.A. Bakar; Susi Endrini, Susi Endrini; Sri Kartini, Sri Kartini; Azman Mohamad, Azman Mohamad; Ahmad F.M. Hanafi, Ahmad F.M. Hanafi (2023)
Secondary plant metabolites play important role as potent drug candidates against antibacterialresistant pathogens such as Klebsiella pneumoniae which commonly causes pneumonia. Red ginger (Zingiber officinale var. rubrum) and black turmeric (Curcuma caesia) from the Zingiberaceae family are the potential plants as antibacterial agents. This study aimed to determine the ability of antibacterial activity and the inhibition mechanism of red ginger, black ginger and mixed (red ginger and black turmeric) extracts on the growth of K. pneumoniae. The method used was in vitro testing using the dilution method. Results showed that red ginger, black ginger and mixed ethanol extracts could inhibit K. pneumoniae growth at concentrations of 125 µg/mL and 250µg/mL, respectively, with a marked decrease in absorbance values before and after incubation. Further observations on bacterial cell leakage showed that the higher concentration of mixed ethanol extract, red ginger and black turmeric, the higher the leakage of K. pneumoniae bacterial cells seen from the increase in absorbance values that could be captured by wavelengths of 260 nm and 280 nm, respectively. Based on scanning electron microscope (SEM), the quantity of K. pneumoniae after treating black turmeric, red ginger, and mixed ethanol extracts decreased, and the cell walls became wrinkled and destroyed. Hence, ethanol extract from red ginger and black turmeric can be recommended as an alternative natural antibacterial in inhibiting the growth of K. pneumoniae, which causes pneumonia infection.